2011
DOI: 10.5966/sctm.2011-0019
|View full text |Cite
|
Sign up to set email alerts
|

Concise Review: Mesenchymal Stem Cells and Translational Medicine: Emerging Issues

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
251
0
9

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 295 publications
(262 citation statements)
references
References 107 publications
2
251
0
9
Order By: Relevance
“…Preliminary investigations have been carried out in different autoimmune diseases like multiple sclerosis, Crohn's disease, systemic lupus, type 1 diabetes mellitus, systemic vasculitides, SSc, and in graft-versushost disease (39,42). In addition, because of their potential angiogenic effects, MSCs have been proposed to be useful in the treatment of various vascular ischemic conditions (31).…”
Section: Discussionmentioning
confidence: 99%
“…Preliminary investigations have been carried out in different autoimmune diseases like multiple sclerosis, Crohn's disease, systemic lupus, type 1 diabetes mellitus, systemic vasculitides, SSc, and in graft-versushost disease (39,42). In addition, because of their potential angiogenic effects, MSCs have been proposed to be useful in the treatment of various vascular ischemic conditions (31).…”
Section: Discussionmentioning
confidence: 99%
“…2,3 MSCs are non-hematopoietic spindle-shaped fibroblast-like cells derived from the mesoderm. 4 MSCs possess self-renewal and immunomodulatory properties, are capable of transdifferentiation, and participate in wound healing, bone regeneration, angiogenesis, and homeostasis. [5][6][7] Due to these characteristics, MSCs therefore, tumors are sometimes called wounds that do not heal.…”
Section: Introductionmentioning
confidence: 99%
“…The therapeutic potential of transfused MSCs has been demonstrated in animal models of experimental autoimmune encephalitis, diabetes, rheumatoid arthritis, myocardial infarction, acute lung injury, retinal degeneration, acute renal failure, and transplant rejection (9,10). In human phase II clinical trials, MSCs were shown to be effective in treating graft-versus-host disease (11), although study of an industrial MSC product in a phase III trial was negative (12)(13)(14).…”
mentioning
confidence: 99%